Students’ Perception Toward English Club Extracurricular in Speaking Practice at MTs Al-Islah Jenggawah - M. Rizky Awang; As’ari As’ari; Dewi Nurul Qomariyah; Muhammad Muizul Hanani (Jurnal Wahana Literasi Pendidikan, 2026)
Speaking is one of the most essential yet most challenging skills for EFL learners. Limited practice opportunities and high anxiety in formal classrooms remain major barriers for Indonesian students. Although previous studies by Armita (2019) and Atika (2024) have examined students' perceptions of English Club extracurricular activities, those studies were conducted at the senior high school level, leaving a gap at the junior high school level within a pesantren environment. This study employed a descriptive qualitative approach with 16 Grade VIII students at MTS Al-Islah Jenggawah selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and document review, then analyzed using the Miles and Huberman interactive model with source and method triangulation. The findings revealed that the English Club was implemented through five systematic stages — warm-up, main activity, presentation, feedback, and closing — using materials progressively contextualized to students' daily and pesantren life. Students held both positive perceptions, including a comfortable atmosphere, increased confidence, and vocabulary development, and negative perceptions, including public speaking anxiety, limited vocabulary, and insufficient meeting frequency. It is concluded that the English Club has been implemented effectively and contributed positively to students' speaking development, although vocabulary-building activities, graduated speaking tasks, and increased meeting frequency are recommended for further improvement.